Apps to Promote Computational Thinking and Coding Skills to Young Age Children: A Pedagogical Challenge for the 21st Century Learners - Stamatios Papadakis (Educational Process: International Journal)
Background/purpose – At the beginning of the 21st century, Computational Thinking (CT) and coding were typically considered part of secondary education programs, focusing on programming and algorithm development. The early childhood classroom was not expected to find students who developed coding skills. Nevertheless, as has been the case lately, CT and coding have been characterized as fundamental skills of the 21st century, not only for computer scientists but all for citizens. However, through developmentally appropriate technologies, the development of coding skills is increasingly possible, and the result may be the advancement of CT fluency or at least familiarity in young age children. Given the enormous success of smart mobile devices and accompanying mobile apps, the question is whether apps provide the children of preschool and pre-primary school age with opportunities to cultivate their basic coding and CT skills. This study is a review article that presents a brief literature review on the apps that promote themselves that can cultivate CT and coding skills of young students.